How to improve the COVID-19 health education strategy in impoverished regions: a pilot study - Huimin Wang; Rujun Liao; Xin Chen; Jie Yu; Tianyu Zhu; Qiang Liao; Tao Zhang (BMC, 2022)
Abstract Background It is of great challenge to raise the public coronavirus disease 2019 (COVID-19) related health literacy (CRHL) in impoverished regions due to the limits of poor infrastructure, large proportion of vulnerable groups, etc. However, those limits cannot be solved in the short term. Therefore, this study chose Liangshan Yi Autonomous Prefecture, one of the poorest areas in China, as a pilot, to reveal the quantitative relationships among different dimensions under the COVID-19 health education framework, clarify the key points for health promotion, and provide specific suggestions for COVID-19 health education strategy in impoverished regions. Methods A cross-sectional questionnaire survey was conducted in five regions of Liangshan Yi Autonomous Prefecture in 2020. There were 2,100 individuals sampled by multi-stage method. This survey mainly measured the four dimensions: CRHL, COVID-19 related tense psychological reactions (CRTPR), COVID-19 related information report acquisition (CRIRA), and general health literacy (GHL). The multivariate logistic regression was used to explore the influence of demographic characteristics on each dimension. Furthermore, to quantify the relationships among different dimensions, this study employed the structural equation model (SEM), and analyzed the mediating effects of CRHL and CRIRA as well as the moderating effects of regional characteristic variables. Results The CRHL played an important role in promoting COVID-19 health education, reaching 52.5% in Liangshan Yi Autonomous Prefecture. The GHL (β = 0.336) and age (β = 0.136) had statistically positive impacts on CRHL. The CRHL affected CRTPR negatively (β = − 0.198) and CRIRA positively (β = 0.052). The CRHL played significant mediating roles among the four dimensions (P < 0.05). Effectiveness of government prevention and control as well as the ethnicity moderated not only the relationships between CRHL and other dimensions, but also the mediating effect of CRHL (P < 0.05). People with lower income and education levels had lower GHL (β = 0.286, 1.292). The youth were more likely to show CRTPR (β = − 0.080). Conclusions By proposing and verifying the theoretical framework, this study put forward specific suggestions on how to improve COVID-19 health education strategies in impoverished regions via implementation methods, key groups and effect evaluation, which also provided references about future public health emergencies for other impoverished regions of the world. Graphical Abstract